Exploring the Opinion Sharing Patterns among Social Media users in Pakistan - Zilehuma,; Zahid Yousaf , (Journal of Peace, Development and Communication, 2021)
The spiral of silence theory described that when majority opinion is dominant the minority opinion is not expressed. Form last five decades, the theory of spiral of silence describes social separation due to minority opinions. The fear of isolation has made individuals frightened in exchanging their opinions. The people who have opinions in minority are the main actors feared from isolation. In today’s world, internet has showed rapid developments and day by day users are getting attracted to this new technology. Social networks attracted a wide variety of public. Social networks are the main indicators of technological hybrid community. Social media has gone beyond expectations of society and goes unreal in its nature. Extended networks and communication technology has extended the individual interest into these networks. This study is an effort to determine the level of effects of spiral of silence on to young generation of Pakistan. This research focus on spiral of silence and the way people are expressing their opinions while having the quasi statistical context in the background. There are many obstacles in opinion expression. There are many variables which are affecting the opinion sharing process using social media. This research uses the spiral of silence theory in relation to the social media usage patterns of its users. It is assumed in this research that fear of isolation, willingness to speak and climate of opinion are the reason to stay silent while using social media. The study indicates that the relationship between dependent and independent variables is strong and positive.